Anthropogenic Morphogenesis of the Kumo-Manych Depression - P. Didenko; I. Katorgin; D. Yurin; A. Roman (Наука. Инновации. Технологии, 2022)
Introduction: the paper considers the influence of human economic activity as an exogenous relief-forming process that affects the emergence of new forms of relief associated processes. The factors and forms of anthropogenic changes in the landscape are considered and the reasons for these changes are revealed. Materials and methods of the research: to determine the degree of influence of dangerous morphogenetic processes on the economic infrastructure on the territory of the Kumo-Manych depression, the structure of morphogenetic processes was determined. The results of the study and their discussion: the Kumo-Manych depression is characterized by the development of a whole complex of negative natural processes associated with both specific natural and climatic conditions and a high degree of anthropogenic load. Economic activity has intensified the processes of desertification. Groups of factors that have a significant impact on changes in morphogenetic processes are identified. Conclusions: the study made it possible to identify groups of facts and describe their share of participation in the morphogenetic transformation of the landscape. The first group is salinity - 61-42%. The second group consists of related processes - flooding and desertification and flooding. The third group consists of secondary erosion processes: wind and water erosion. The fourth group consists of morphogenetic processes expressed in: waterlogging, sedimentation, and abrasion. The contribution of other dangerous morphogenetic processes is insignificant. Among them, we can note the unfavorable processes of ravine formation.